ANALYSIS OF THE CREDIT ACTIVITY OF ISLAMIC BANKS IN IRAQ OVER THE PERIOD (2004 – 2022) (World Economics and Finance Bulletin, 2024)
The research aims to analyze the credit activity of Iraqi Islamic banks, as there has been a noticeable development and widespread expansion of Islamic banks in the last decade in many countries around the world, especially in Iraq. To achieve this goal, we analyzed a sample of Islamic banks in Iraq that are active in the Iraq Stock Exchange, due to the availability of their annual financial data for the period (2004-2022). We examined their credit activity as a result of using Islamic financing methods. The most significant finding of the research is The increased entry of Islamic banks into the Iraqi banking sector, which reached (23) Islamic banks operating in 2022. Additionally, there was an increase in the total credit activity of Islamic banks during our study period, particularly in 2022, as a result of the rise in the number of Islamic banks in the banking sector. His main recommendations : Encouraging Islamic banks to develop their investment activities by diversifying Islamic financing methods and increasing their role in the process of development and economic growth .